Answer:
consider an example [tex]f(x)=-x^{2}+4[/tex].
Step-by-step explanation:
hunter says that for a function between x= -2 and x=2, the average rate of change is 0.
the average rate of a change of a function between the points a and b is given by:
[tex]\dfrac{f(b)-f(a)}{b-a}[/tex]
for it to be equal to zero we have f(a)=f(b).
hence according to Hunter f(-2)=f(2).
Now maggie says that for the function between x=-2 and x=2 the graph goes up through a turning point and back down.
for both of them to be correct we can consider the example [tex]f(x)=-x^{2}+4[/tex].